2020
DOI: 10.1002/admi.202001638
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Based Synthesis of Gold Single Atoms‐Embedded, Metal–Organic Frameworks‐Derived Nanoporous Carbon Nanoparticles with Enhanced Reduction Ability

Abstract: Single‐atom catalysts (SACs) have emerged to be a new research frontier in catalysis due to their distinctive physical and chemical properties, including better catalytic performance, stability, and recyclability. However, the widely used organic synthesis methods for SACs limit the ability to uniformly distribute single atoms’ water‐soluble precursors on the support of the catalysts. A water‐based synthesis of single gold (Au) atom catalyst is used in this work. Through this method, water‐soluble Au precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…We have previously reported that ZIF-8, ZIF-90, and MIL-100 can be synthesized using water as a solvent in bulk solution. 31,34,35 We also reported a de novo approach for the production of biocatalysts via embedding enzymes into nanoporous materials and for simultaneous encapsulation of metal nanoparticles in the self-assembly of porous materials. 36–38 Herein, we demonstrate the synthesis of ZIF-8 and MIL-100 using a water-based droplet microfluidic flow system with precise control of temperature, time, and flow rates.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that ZIF-8, ZIF-90, and MIL-100 can be synthesized using water as a solvent in bulk solution. 31,34,35 We also reported a de novo approach for the production of biocatalysts via embedding enzymes into nanoporous materials and for simultaneous encapsulation of metal nanoparticles in the self-assembly of porous materials. 36–38 Herein, we demonstrate the synthesis of ZIF-8 and MIL-100 using a water-based droplet microfluidic flow system with precise control of temperature, time, and flow rates.…”
Section: Introductionmentioning
confidence: 99%